(C^Npz^C)AuIII complexes of acyclic carbene ligands: synthesis and anticancer properties. Issue 39 (25th September 2017) - Williams, Morwen; Green, Adam I.; Fernandez-Cestau, Julio; Hughes, David L.; O'Connell, Maria A.; Searcey, Mark; Bertrand, Benoît; Bochmann, Manfred
Abstract : Synthesis of amino ester conjugated (C^N pz ^C)Au acyclic carbene complexes with low micromolar cytotoxicity on human cancer cells. Abstract : A series of cyclometallated gold(iii ) complexes supported by pyrazine-based (C^N pz ^C)-type pincer ligands were synthesized via two different pathways. Nucleophilic attack on the isocyanide complex [(C^N pz ^C)Au(CNC6 H3 Me2 -2, 6)]SbF6 (2 ) gave [(C^N pz ^C)Au(ACC)]SbF6 complexes with aniline (4 ·SbF 6 ), adamantylamine (5 ), glycine ethyl ester (6 ), alanine methyl ester (7 ), valine methyl ester (8 ), phenylglycine methyl ester (9 ) and methionine methyl ester (10 ) substituents (ACC = acyclic carbene). The pathway via isocyanide insertion into gold–amide bonds was also investigated; e.g. the reaction of xylyl isocyanide with (C^N pz ^C)AuNHPh followed by protonation with HBF4 ·OEt2 gave the acyclic carbene complex4 ·BF 4 . To the best of our knowledge compounds6–10 represent the first examples of gold(iii ) acyclic carbene complexes bearing amino acid functions. The compounds provide a versatile platform for the study of the anti-proliferative properties of gold(iii ) complexes. Tests against human adenoma-type lung cancer cells identified5, 6, 7 and10 as particularly promising and demonstrate the synthetic flexibility of acyclic carbene complexes and the potential of that class of compounds for anticancer applications. Compared to cisplatin, amino ester-containing ACC complexes showed improved selectivity for MCF-7 breast cancer cells over that for healthy fibroblasts.